Influence of collaboration on ESL learner’s fluency and accuracy in writing - Wahab, Nashatul Azwa (2016)
This quasi-experimental study investigated the effect of collaborative writing on the tertiary level students’ fluency and accuracy in ESL writing. This study also looked at how students communicate their ideas during the collaborative process and through this the nature of interaction during collaborative writing were identified. This study utilised a mixed-methods design that was a combination of quantitative and qualitative approaches. The researcher used Mann Whitney U-test to compare the performance of the students in terms of fluency and accuracy measures. Content analysis was conducted on the interaction transcriptions to investigate how the students communicate their ideas and the nature of the interaction during the collaborative process. The participants were 69 first year students of mixed ability level in Universiti Sultan Zainal Abidin, Kuala Terengganu and they have to attend English Language Proficiency course that focused more on their writing skill. The objectives of this study were to find out the differences in terms of fluency and accuracy in the students’ writing when they wrote individually and collaboratively. Secondly, this study aimed to investigate how the students communicate their ideas during their collaboration process with their peers. Using stratified random sampling, the participants were separated into two groups: the control group and the experimental group. Both groups underwent the same learning process but at the end of the process, the control group produced their essay individually and the experimental group had to produce their essay collaboratively. They were observed by the researcher and their discussions were recorded. Findings showed that there were significant differences in terms of the students’ accuracy in their writing especially in terms of grammatical accuracy and lexical choice. However, no difference was found in terms of their fluency of writing. The recorded transcriptions indicated that the most frequently discussed topic by the students was lexical items, followed by grammatical issues and mechanics of writing. From the recorded conversation, five features of interaction were identified during the students’ collaborative writing activity namely mutual interaction, negotiation, cognitive conflict, shared expertise and use of L1. It could be concluded that collaborative writing could provide much assistance for the students in producing an accurate text. Besides that, this type of learning could open up opportunities for the students to be engaged in a productive academic discussion with their friends in their L2 writing classroom.